Structural Variants in SNCA Gene and the Implication to Synucleinopathies - Chiba-Falek, Ornit (Curr Opin Genet Dev, 2017)
Synucleinopathies are a group of neurodegenerative diseases that share a common pathological lesion of intracellular protein inclusions largely composed of aggregates of alpha-synuclein protein. Accumulating evidence, including genome-wide association studies, has implicated the alpha-synuclein (SNCA) gene in the etiology of synucleinopathies and it has been suggested that SNCA expression levels are critical for the development of these diseases. This review focuses on genetic variants from the class of structural variants (SVs), including multiplication of large genomic segments and short (<50bp) genomic variants such as simple sequence repeats (SSRs), within the SNCA locus. We provide evidence that SNCA-SVs play a key role in the pathogenesis of synucleinopathies via their effects on gene expression and on regulatory mechanisms including transcription and splicing.